IMPROVING SCIENCE LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING MODELS ASSISTED BY MIND MAPPING MEDIA - Binti Umi Malikah; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Good learning should be able to train students to think optimally. This classroom action research was conducted with the aim of knowing an increase in science learning outcomes through the application of the Problem Based Learning learning method assisted by Mind Mapping in grade 5. There were two cycles carried out in this classroom action research with several stages, namely planning, action and observation, and reflection. The collected data was then analyzed using quantitative data analysis techniques. The results showed that there was an increase in the mastery of student learning outcomes from the pre-cycle stage to the second cycle. In the pre-cycle completeness learning outcomes are 44%, namely 8 students complete in class out of a total of 20 students. In the pre-cycle there were 13 students who finished with a percentage of 65% and in the second cycle the number of students who finished again increased to 16 students with a percentage of 80%. This shows that the problem-based learning model with the aid of mind mapping media can improve the learning outcomes of fifth grade students at SDN Munungrejo 1 in science learning Theme 9 Sub-theme 1 peningkatan hasil belajar IPA melalui penerapan metode pembelajaran Problem Based Learning berbantuan Mind Mapping di kelas 5. Ada dua siklus yang dilaksanakan dalam penelitian tindakan kelas ini dengan beberapa tahapan, yaitu perencanaan, tindakan dan observasi, serta refleksi. Dalam penelitian ini, peneliti mengambil materi di Kelas 5 Tema 9 Benda – Benda di Sekitar Kita Subtema 1 Benda Tunggal dan Campuran. Adapun subyek yang digunakan adalah siswa kelas 5 SDN Munungrejo I yang berjumlah 20 siswa, 9 siswa laki – laki dan 11 siswa perempuan. Penelitian ini dilaksanakan pada semester genap tepatnya di bulan April – Juni tahun ajaran 2021/2022. Teknik pengumpulan data dalam penelitian tindakan kelas ini menggunakan teknik wawancara, observasi, tes, dokumentasi, dan catatan lapangan.